A Case of Bilateral Pigment Dispersion Syndrome Following Many Years of Uninterrupted Treatment With Atropine 1% for Bilateral Congenital Cataracts. Issue 10 (October 2017) - Gizzi, Corrado; Mohamed-Noriega, Jibran; Murdoch, Ian
Abstract : Purpose: Describe an unusual case of bilateral pigment dispersion syndrome (PDS) following years of uninterrupted treatment with atropine 1% for bilateral congenital cataracts, speculate on potential mechanisms leading to this condition. Design: This is a case report. Case: A 45-year-old white patient on long-term treatment with atropine 1% ointment since his infancy for bilateral congenital cataracts developed PDS with secondary ocular hypertension. Results: The patient showed all the hallmarks of PDS with secondary ocular hypertension. An anterior segment Swept-Source optical coherence tomography was obtained to review the iris profile. The patient showed good pressure response to topical prostaglandin therapy. Conclusions: This is the second case report of PDS in a patient with chronic use of topical atropine. The proposed mechanisms for pigment dispersion are discussed and the possibility raised of dispersion being a potential side effect of the drug.